2019
DOI: 10.1111/faf.12400
|View full text |Cite
|
Sign up to set email alerts
|

Shifting perceptions of rapid temperature changes’ effects on marine fisheries, 1945–2017

Abstract: Climate‐driven warming has both social and ecological effects on marine fisheries. While recent changes due to anthropogenic global warming have been documented, similar basin‐wide changes have occurred in the past due to natural temperature fluctuations. Here, we document the effects of rapidly changing water temperatures along the United States’ east coast using observations from fisheries newspapers during a warming phase (1945–1951) and subsequent cooling phase (1952–1960) of the Atlantic Multidecadal Osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…We found that, in all but two of our focal communities, catch diversity declined between the two time periods examined (Figure 8 top). This aligns with the region-wide trend toward vessels catching fewer species and/or becoming more specialized (Seara, 2014;Stoll et al, 2016;McClenachan et al, 2019), and it suggests higher levels of vulnerability for many communities, especially when compounded by declines in numbers of vessels and fisher-days (Supplementary Table B1) even as catch per trip increases in, for example, the large trawl communities of Gloucester, New Bedford, and Montauk (Supplementary Table B1).…”
Section: Shifts In Target Speciessupporting
confidence: 65%
“…We found that, in all but two of our focal communities, catch diversity declined between the two time periods examined (Figure 8 top). This aligns with the region-wide trend toward vessels catching fewer species and/or becoming more specialized (Seara, 2014;Stoll et al, 2016;McClenachan et al, 2019), and it suggests higher levels of vulnerability for many communities, especially when compounded by declines in numbers of vessels and fisher-days (Supplementary Table B1) even as catch per trip increases in, for example, the large trawl communities of Gloucester, New Bedford, and Montauk (Supplementary Table B1).…”
Section: Shifts In Target Speciessupporting
confidence: 65%
“…The link between fast life history and the strength of the global warming impact on fished stocks has also been recently confirmed by Free et al (2019). And last, but not the least, global change exerts its fishery relevant effect due to declining ecosystem diversity, decreased resilience of exploited stocks, and temperature dependent distribution shifts (Perry et al 2005;McClenachan et al 2019). Such distribution shifts have been already documented for cephalopod species, including the octopuses (Ramos et al 2018).…”
Section: Why Is the Evolutionary Toolbox Needed In Cephalopod Fisheries?mentioning
confidence: 77%
“…Elevated seawater temperature has severely affected the biological activity of marine organisms including scallops, resulting in massive losses to fisheries in recent years [ 6 , 7 ]. In order to investigate the functions of AiPC4s in bay scallops under high-temperature stress, expression profiles of AiPC4s were detected in four tissues (mantles, gills, hearts, and hemocytes), which are all regarded as the major tissues in response to thermal stress in mollusks [ 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, coral reefs were the ecosystems most vulnerable to environmental impacts, removing substantial amounts of living coral with a warming climate [ 4 , 5 ]. Marine ecosystems have been significantly affected by elevated seawater temperature [ 6 ], and climate warming has also caused incalculable losses to fisheries for many years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%